Osteocytic Protein Expression Response to Doxercalciferol Therapy in Pediatric Dialysis Patients - Pereira, Renata C.; Jüppner, Harald; Gales, Barbara; Salusky, Isidro B.; Wesseling-Perry, Katherine (PLOS ONE, 2015)
Background Osteocytic protein expression is dysregulated in CKD and is affected by changes in mineral metabolism; however the effects of active vitamin D sterol therapy on osteocyte protein expression in advanced CKD is unknown. Methods Eleven pediatric patients with end stage kidney disease underwent bone biopsy, were treated for 8 months with doxercalciferol, and then underwent a second bone biopsy. Bone expression of fibroblast growth factor 23 (FGF23), dentin matrix protein 1 (DMP1), and sclerostin were determined by immunohistochemistry and quantified by Ariol Scanning. Western blot analysis and qRT-PCR was performed on bone abstracts of a subset of study subjects to determine the nature (i.e. size) of FGF23 and DMP1 in bone before and after therapy. Results As assessed by immunohistochemistry, bone FGF23, DMP1 and sclerostin protein all increased with therapy. In the case of FGF23, this increase was due to an increase in the full-length molecule without the appearance of FGF23 fragments. DMP1 was present primarily in its full-length form in healthy controls while 57kDa and 37kDa fragments of DMP1 were apparent in bone of dialysis patients at baseline and the 57 kDa appeared to decrease with therapy. Conclusion Marked changes in osteocytic protein expression accompany doxercalciferol therapy, potentially impacting bone mineralization and the skeletal response to PTH. The effects of these bone changes on long-term outcomes remain to be determined.